Retrospective Assessment of Legal Capacity After Death: Experience of Hacettepe University Faculty of Medicine, Department of Forensic Medicine - İğde, Emre Nuri; Cavlak, Mehmet; Genç, Neslihan; Elden, Uğur; Akçan, Ramazan; Balseven Odabaşı, Aysun (The Bulletin of Legal Medicine, 2024)
Objective: This study aims to contribute to the literature by presenting our department’s experience in retrospective assessment of legal capacity, occasionally encountered in clinical forensic medicine.Methods: Forensic psychiatry reports prepared at Hacettepe University Faculty of Medicine, Department of Forensic Medicine between 01.01.2021 and 31.03.2024 were examined retrospectively. Cases who underwent retrospective legal capacity evaluation after death were included in the study. The demographic characteristics such as age and gender of the cases, their medical and psychiatric histories, causes of death, witness statements and visual records available in the forensic investigation files, as well as health reports pertaining to legal capacity dated prior to the incidents, were evaluated.Results: Five cases were male, one was female. Ages ranged from 81 to 96, with a mean of 88.2. All had at least one chronic illness; four had dementia. Two did not have health reports at the contract date; in four cases with health reports, legal capacity was noted. Forensic psychiatry reports prepared by our department indicated indicated legal capacity in three cases, absence in two, and inconclusiveness in one.Conclusion: In the majority of cases where retrospective legal capacity assessment following death is requested, a diagnosis of dementia is prevalent. The inability to examine the cases necessitates a meticulous and standardized evaluation. Scientific adequacy of the medical report prepared at the time of the incident should be scrutinized. Following examination of medical and legal documents, a forensic psychiatry report should be prepared meticulously and in accordance with reasoned and scientific criteria.
Keywords: forensic psychiatry; legal capacity; dementia; retrospective legal capacity assessment